Measurement of Candidacidal Activity of Specific Leukocyte Types in Mixed Cell Populations II. Normal and Chronic Granulomatous Disease Eosinophils - Lehrer, Robert I. (1971)
Normal human eosinophils possess appreciable intrinsic candidacidal activity. The leukocyte microbicidal deficiency of chronic granulomatous disease is manifested by eosinophils as well as by neutrophils and monocytes.